Women of color and the reproductive rights movement - Nelson, Jennifer (New York University Press, 2003)
While most people believe that the movement to secure voluntary reproductive control for women centered solely on abortion rights, for many women abortion was not the only, or even primary, focus.Jennifer Nelson tells the story of the feminist struggle for legal abortion and reproductive rights in the 1960s, 1970s, and early 1980s through the particular contributions of women of color. She explores the relationship between second-wave feminists, who were concerned with a woman's right to choose, Black and Puerto Rican Nationalists, who were concerned that Black and Puerto Rican women have as many children as possible "for the revolution," and women of color themselves, who negotiated between them. Contrary to popular belief, Nelson shows that women of color were able to successfully remake the mainstream women's liberation and abortion rights movements by appropriating select aspects of Black Nationalist politics–including addressing sterilization abuse, access to affordable childcare and healthcare, and ways to raise children out of poverty–for feminist discourse.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; discipline; femmes* de couleur; histoire; justice reproductive; militance; périodes historiques; régions géographiques; sciences humaines; sociologie; sofia; thématiques; états-unis

Killing the Black Body: race, reproduction, and the meaning of liberty - Roberts, D. (Pantheon, 1997)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; histoire et politique; inégalités; justice reproductive; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis